Coping with changing environments: social dimensions of endangered ecosystems in the developing world - Lohnert, Beate; Geist, Helmut (Routledge, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- List of Figures -- List of Tables -- List of Contributors -- Foreword -- Acknowledgements -- List of Abbreviations -- 1 Endangered Ecosystems and Coping Strategies Towards a conceptualization of environmental change in the developing world -- 2 Coping with Vulnerability and Unsustainability The case of Nepalese upland farmers -- 3 Hydropower, Rice Farmers and the State The case of deforestation in Laos -- 4 Debating Vulnerability, Environment and Housing The case of rural-urban migrants in Cape Town, South Africa -- 5 Soil Mining and Societal Responses The case of tobacco in eastern Miombo highlands -- 6 Changes of Land Use and Institutions in Natural Resource Management The case of the Tanzanian Maasailand -- 7 Drought Hazards and Threatened Livelihoods Environmental perceptions in Botswana -- 8 Environmental Conservation, Land Tenure and Migration The case of the Atlantic rainforest in southeast Brazil -- 9 Why Herd Animals Die Environmental perception and cultural risk management in the Andes -- 10 Risks and Coping Strategies of a Vulnerable Group in the Dominican Dry Forest The case of charcoal burners in Chalona -- 11 Actors, Structures and Environments A comparative and transdisciplinary view on regional case studies of global environmental change -- Index of Authors -- Index of Subject Matters
Keywords: Developing countries -- Social conditions; Konferenzschrift; Aufsatzsammlung; Umweltpolitik; Gesellschaft; Umwelt; Entwicklungsländer; Umweltschutz; Umweltgefährdung; Umweltveränderung; Ökosystem